In vitro photoacoustic sensing of calcium dynamics with arsenazo III. (10th June 2016) - Dana, N; Fowler, R A; Allen, A; Zoldan, J; Suggs, L; Emelianov, S
Abstract: Imaging of cellular electric potential via calcium-ion sensitive contrast agents is a useful tool, but current techniques lack sufficient depth penetration. We explore contrast-enhanced photoacoustic (PA) imaging, using Arsenazo III dye, to visualize cardiac myocyte depolarization in vitro . Phantom results show strong linearity of PA signal with dye concentration ( R 2 > 0.95), and agree spectrally with extinction measurements with varying calcium concentration. Cell studies indicate a significant (>100-fold) increase in PA signal for dye-treated cells, as well as a 10-fold increase in peak-to-peak variation during a 30 s window. This suggests contrast-enhanced PA imaging may have sufficient sensitivity and specificity for depth-resolved visualization of tissue depolarization in real-time.